Biocompatible organic electrochemical transistor on polymeric scaffold for wound healing monitoring. (1st September 2022) - Cavallo, Aida; Losi, Paola; Buscemi, Marianna; Kayal, Tamer Al; Beccatelli, Matteo; Soldani, Giorgio; Coppedè, Nicola
Abstract: Nowadays, no wearable device is available to continuously monitor the ulcer status. The literature reports a pH range between 6.5 and 9 for chronic or infected wounds. This study aims to produce an innovative scaffold able to monitoring wound pH and therefore ulcers healing. The scaffold was manufactured by spray, phase-inversion technique using a synthetic biocompatible material, poly(ether)urethane-polydimethylsiloxane (PEtU-PDMS). A bi-layer micro-fibrillar tubular scaffold was obtained using: (a) 2% polymer solution and H2 O as non-solvent; (b) 0.2% and H2 O. Poly(3, 4‐ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) is a biocompatible conductive polymer used as active material in a biosensor due to high sensitivity to positive ions in liquid environment allowing to determine ions concentration in easy and stable way. The biocompatible scaffold was functionalized by inkjet-printing of a PEDOT:PSS to develop organic electrochemical transistor (OECT) architecture. The electrochemical device was connected with electric contacts to create a channel and a gate electrode to control the modulation changes of the sensor. The morphological analysis of PEtU-PDMS scaffold surfaces was performed using a stereo-microscope after Sudan Black B staining while the PEDOT:PSS pattern by SEM microscopy. The device functionality was proved on human serum at different pH (between four and ten). The morphological analysis showed a dense, non-porous surface obtained with the 2% solution, while a porous surface was obtained with the 0.2% solution where the PEDOT:PSS was positioned. This feature, maintained after lyophilization and re-hydratation, enables a thin PEDOT:PSS film deposition in a continuous and homogeneus pattern. The characteristic of the device was tested showing the sensitivity to saline concentration and the effective functionality of the device. Moreover, the device response shows a dependence to pH variations as well as the transconductance. Obtained data suggest that the proposed sensorised scaffold could be used as a wearable detector for wound healing monitoring in patients affected by chronic lesions.